2007
DOI: 10.1177/117863370700200005
|View full text |Cite
|
Sign up to set email alerts
|

Platelet Aggregation Inhibitors from Aerial Parts of Ruta Chalepensis Grown in Jordan

Abstract: Abstract:From the aerial parts of Ruta chalepensis L., grown in Jordan, two furanocoumarins (bergapten and chalepensin), one fl avonoid glycoside (rutin) as well as several minor compounds have been isolated. The structural elucidation of these compounds was established based on spectral data (UV, IR, MS, 1 H-NMR and 13 C-NMR). In Jordan, R. chalepensis is recommended for the treatment of rheumatism, mental disorders and menstrual problems. Fresh and dried leaves are used as fl avoring agent in food and bevera… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
9
0
1

Year Published

2011
2011
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(11 citation statements)
references
References 30 publications
(29 reference statements)
1
9
0
1
Order By: Relevance
“…The genus Ruta features Shrubby plants that are native to the Mediterranean region and are represented by 40 species in the world [18], which were used as traditional medicine in many countries to treat a variety of diseases such as rheumatism, neuralgia, menstrual bleeding, fever, arthritis, hepatic diseases, antifertility, and gastrointestinal disorders [19]. Also, recent studies [20][21][22], revealed that rue species have analgesic, antipyretic, anti-inflammatory, antifungal, emmenagogue, insect repellent, molluscicidal, nematicidal, antimicrobial, anthelmintic, sedative, and antiplatelet properties. R. graveolens is a small aromatic shrub cultivate in Egypt and known for its medicinal aromatic properties, since ancient times [23].…”
Section: Introductionmentioning
confidence: 99%
“…The genus Ruta features Shrubby plants that are native to the Mediterranean region and are represented by 40 species in the world [18], which were used as traditional medicine in many countries to treat a variety of diseases such as rheumatism, neuralgia, menstrual bleeding, fever, arthritis, hepatic diseases, antifertility, and gastrointestinal disorders [19]. Also, recent studies [20][21][22], revealed that rue species have analgesic, antipyretic, anti-inflammatory, antifungal, emmenagogue, insect repellent, molluscicidal, nematicidal, antimicrobial, anthelmintic, sedative, and antiplatelet properties. R. graveolens is a small aromatic shrub cultivate in Egypt and known for its medicinal aromatic properties, since ancient times [23].…”
Section: Introductionmentioning
confidence: 99%
“…In addition, Ruta chalepensis is recorded as possible apportion factor among pregnant women, eliciting its prospect effect on the circulatory system. This coincided with its use in traditional medicine in menstrual problems as was proved to have antiplatelet activities [28]. The remaining examined plant species were chosen due to their other recorded bioactivities [22].…”
Section: Introductionmentioning
confidence: 99%
“…Bergapten is a fumaro-coumarin, which has acquired a place in the treatment of psoriasis and other dermatoses [1] . It also showed platelet aggregation inhibitory activity [2] .…”
mentioning
confidence: 99%